Blockchain: A Technological Revolution in the Financial Sector-The Singapore Experience: Projects) Ubin, Orchid, Guardian (Journal of Economic Additions, 2026)
Blockchain has pillar of modern finance, attracting younger generations through its ability to transform financial information management in a connected world. Its adoption reshapes financial infrastructure and practices to meet digital demands, serving as a tool for transparency and efficiency. This study examines blockchain’s role in the financial sector using a descriptive- analytical approach, outlining concepts and analyzing applications in Singapore.Findings show blockchain simplifies banking operations, reduces costs, and signals institutions’ move toward a more flexible future. Regulatory and legal challenges remain, requiring efforts to overcome barriers. Addressing these issues is essential for adoption, efficiency, and innovative financial solutions.Jel Classification Codes : G23, G2
Keywords: Blockchain Technology; Financial Sector; Singapore